A longitudinal study of organizational stressors and mental health in the Irish Olympic team before and after the "Tokyo 2020" (2021) Olympic Games - Browne, J.-A.; Paradis, K. F.; Kirby, K.; Arnold, R. (The Sport Psychologist, 2025)
Aims: The primary aim of the present study was to assess the relationship between organizational stressors and mental health and well-being indicators of the Irish Olympic Team before and after the "Tokyo 2020" Olympic Games. A secondary aim was to examine the differences in mental health and well-being between the athletes and staff of Team Ireland pre- and post-Games. Method: The Irish Olympic Team comprised 271 members (116 athletes and 155 team staff). Participants were sent an online survey package 2 weeks pregames (Time 1) and 4 weeks postgames (Time 2). A total of 98 participants (36% response rate) responded at Time 1, and 70 participants (26% response rate) responded at Time 2. Measures included the Organizational Stressor Indicator for Sport Performers, the Mental Health Continuum-Short Form, and the Sport Mental Health Assessment Tool 1. Results: There was a significant inverse association between organizational stressors and mental well-being at both Time 1 (ß = -0.46) and Time 2 (ß = -0.35) and from pre- to post-Games (ß = -0.48). There was a significant positive association between organizational stressors and risk of mental health symptoms at both Time 1 (ß = 0.69) and Time 2 (ß = 0.67) and from pre- to post-Games (ß = 0.34). At Time 1, team staff (75%) reported significantly greater risk of mental health symptoms than athletes (50%); however, at Time 2, athletes (80%) reported significantly greater risk of mental health symptoms than staff (50%). The overall number of participants flourishing decreased from pre- (43%) to post-Games (31%). Conclusion: Findings have implications for mental health support provision, which tends to be athlete focused but might forget about team staff, and to consider preevent provision but to also not forget about postevent care.